EasiND: Neighbor Discovery in Duty-Cycled Asynchronous Multichannel Mobile WSNs. (31st July 2013) - Huang, Tingpei; Chen, Haiming; Cui, Li; Zhang, Yuqing
Abstract : Neighbor discovery is one of the first steps to establish communication links between sensor nodes; thus it becomes a fundamental building block for wireless sensor networks (WSNs). Traditional neighbor discovery protocols mainly focus on static wireless networks or networks where all nodes operate on the same frequency. However, the proliferation of mobile devices and multichannel communications post new challenges to neighbor discovery problem. In this paper, we present a neighbor discovery protocol named EasiND for asynchronous duty-cycled multichannel mobile WSNs. First, we propose a neighbor discovery system based on quorum system, which can bound the discovery latency in multichannel scenarios with low power consumptions. Second, we design an optimal asynchronous neighbor discovery system for multichannel mobile WSNs based on cyclic difference set. It is optimal in the sense that it minimizes the power consumption with bounded discovery latency under desired duty cycles. Finally, we validate the performance of EasiND through both theoretical analysis and test-bed evaluations. EasiND provides a 33.3% reduction in power-latency product in theory compared to U-Connect. Meanwhile, test-bed evaluation results show that EasiND decreases average discovery latency by up to 86% compared to U-Connect and achieves at least 93.5% average fraction of discoveries in a predefined time limitation under various network conditions.